2009
DOI: 10.1007/s00262-009-0784-6
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival analysis for renal carcinoma patients treated with an autologous tumour lysate vaccine in an adjuvant setting

Abstract: About 30% of renal cell carcinomas (RCC) will develop recurrence after surgery. Despite evidence for a significantly improved survival by autologous tumour cell vaccination therapy, the procedure has not become standard. Between August 1993 and December 1996, 1,267 RCC patients undergoing radical nephrectomy in 84 German hospitals were subsequently treated by autologous tumour cell vaccination therapy. The study group comprised 692 patients with complete follow-up (stages pT2-3, pNx-2, M0 based on the TNM clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…22 Apart from this, knowledge about DAMPs can also help us in improving certain vaccination strategies employed against cancer. For instance, 'autologous' (killed) tumour cell based-vaccines 23, 24 and 'autologous' dendritic cell (DC)-based vaccines 25,26 have shown considerable promise mitigated by instances of failures within clinical settings.…”
Section: Not Known 7879mentioning
confidence: 99%
“…22 Apart from this, knowledge about DAMPs can also help us in improving certain vaccination strategies employed against cancer. For instance, 'autologous' (killed) tumour cell based-vaccines 23, 24 and 'autologous' dendritic cell (DC)-based vaccines 25,26 have shown considerable promise mitigated by instances of failures within clinical settings.…”
Section: Not Known 7879mentioning
confidence: 99%
“…24 The only adjuvant trial with this approach to show a significant benefit in DFS used an autologous RCC lysate vaccine, but the high number of patients lost after randomization (32%), the imbalance of this loss between treatment arms, and the absence of OS data led to criticism of the results 25 ; however, a recent update of the results with 10-year follow up did reveal a benefit in OS, mainly in pT3 patients. 26 Finally, a trial that has recently reported first results is the Adjuvant RENCAREX Ò Immunotherapy trial to Study Efficacy in non-metastasised Renal cell carcinoma trial with girentuximab, a monoclonal antibody that binds the CA-IX cell surface antigen, present in 95% of RCC. This international, randomized, doubleblind phase III trial compared girentuximab with placebo, and enrolled 864 high-risk patients.…”
Section: Immune Therapy Trialsmentioning
confidence: 99%
“…34 Subsequently, a review with 10-year follow-up showed that 5-year overall survival of patients with UICC stage 3 disease was 71.9% in patients receiving autologous vaccine versus 60.3% for those who had surgery alone ( p =0.008). 35 …”
Section: Development Of Tumor Vaccinesmentioning
confidence: 99%